Speech Funtion Analysis in “ Alice In Wonderland” Movie Script - Layun Vera; Abdul Rohman; Widi Syahtia Pane (Inquest Journal, 2023)
AbstractBackground:A language is a tool for communication in this world used by humans to communicate with each other, without language, people get a problem when they want to communicate and a desire to socialize with people. The social functions of communication are explained by the speech function Apparently, speaking has a variety of functions. Many kinds of different speech functions, including phatic, poetic, metalinguistic, expressive, directive, and referential. Speech that people make serves a variety of purposes. This study aims to analyze the kinds of speech functions that are used in Alice In Wonderland Movie.Methodology: The researcher used a design for content analysis. The characters shown in the film "Alice In Wonderland" Movie is the focus of this investigation. The study's focus was on the declarative and interrogative language employed by the movie's characters. A checklist served as the study's main tool.Findings: In this study, the researcher found there are 111 speech functions used by the characters in Alice in Wonderland movie script. The researcher found there are five types of speech functions, 19 expressive speech functions, 39 directives speech functions, 34 referential speech functions, 7 poetic speech functions, and 12 phatic speech functions.Conclusion: In this research the researcher concludes, the referential speech function is the most used type of speech function by the actors in Alice in Wonderland movie because there are 39 directive speech functions found in this movie and the lowest types of speech functions used by the characters is poetic speech function where the researcher found there is only 7 poetic speech function.Originality: This research can used for references and help students or readers to understand deeper the speech function and and know hot utilize them